Die asymptotische Entwicklung für die Verteilungsfunktion der normierten Summen unabhängiger Zufallsgrößen - Survila, P. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Сурвила. Асимптотические разложения для функции распределения нормированной суммы независимых случайных величин P. Survila. Nepriklausomų atsitiktinių dydžių normuotos sumos pasiskirstymo funkcijos asimptotinis išdėstymas